The Lost World of Russia's Jews : Ethnography and Folklore in the Pale of Settlement - Rechtman, Abraham (Jews in Eastern Europe Ser., 2021)
The Lost World of Russia's Jews powerfully illuminates traditional Jewish life in Eastern Europe on the eve of its transformation and, ultimately, destruction.